Multiple choice questions and essay questions in assessment of success rate in medical physiology - Saeed, Ghassan Th.; Hassan, Affan E.; Al Omary, Hanan L.; Alawad, Zainab M. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Assessment is an important part of the learning cascade in education. Students realize it as an influential motivator to direct and guide their learning. The method of assessment determines the way the students reach high levels of learning. It has been documented that one of factor affecting students’ choice of learning approach is the way how assessment is being performed. Many methods of assessment namely multiple choice questions, essay questions and others are mainly used to assess basic science knowledge in undergraduate education. Objectives: The aim of this study is to compare multiple choice questions (MCQ) and essay questions (EQ) (record the success and failure rate of multiple choice questions (MCQ) and essay questions (EQ)) in regards to the Physiology questions. Methods: A retrospective study was done in which the results of the physiology exams -held in the medical college in Baghdad University -in 2010 are recorded. The number of students underwent the exam was 255. A total of 100 essay questions (EQs) and 100 multiple choice questions (MCQs) were evaluated from the written examinations delivered to second year medical students questions belonged to final examination. Results: Regarding essay questions that have been answered, 33.5% of the questions were not answered as a total. 188 students out of 255 had succeeded which represent 73.7% of the students. Out of 78 marks for MCQ, 46.33 had been achieved, and out of 22 marks for essay 12.9 have been achieved. the success in MCQ questions was 82.9% while in the Essay questions was 67.7% and the failure in both types was 12.5%. Out of 100 questions for both MCQ and Essay questions 55.1±7.9 questions were answered for the MCQ and 51.1±15.3 Essay questions were answered. In general the percentage of the succeeded students was 73. 7% and that of failed students was 26.3%. Conclusion: There is no significant difference in the success rate between MCQs and EQs. الخلفية: يعد التقييم عنصرا هاما في سلسلة التعلم في التعليم. يدرك الطلاب أنها حافز مؤثر لتوجيه تعلمهم. ويحدد أسلوب التقييم طريقة وصول الطلبة إلى مستويات عالية من التعلم. وقد تم توثيق أن أحد العوامل التي تؤثر على اختيار الطلاب لموقف التعلم هو طريقة تقييمهم. يتم تطبيق العديد من أساليب التقييم وهي أسئلة الاختيار من متعدد، أسئلة مقالة وغيرها أساسا لفحص العلوم الأساسية الفهم في التعليم الجامعي. الهدف: الهدف من هذه الدراسة هو مقارنة أسئلة الاختيار من متعدد وأسئلة مقال (تقييم نجاح وفشل معدل أسئلة الاختيار من متعدد وأسئلة مقال) فيما يتعلق باسئلة علم وظائف الأعضاء. الطريقة: أجريت دراسة بأثر رجعي تم فيها تسجيل نتائج امتحانات علم وظائف الأعضاء - التي تم تسجيلها في الكلية الطبية لجامعة بغداد - في عام 2010. وبلغ عدد الطلاب الذين خضعوا للامتحان 255. تم تقييم مجموعه 100 أسئلة مقالة و 100 أسئلة الاختيار من متعدد من الامتحانات المكتوبة التي تدار لطلاب الطب السنة الثانية (الأسئلة تنتمي إلى الامتحان النهائي) النتائج: فيما يتعلق بأسئلة المقالات التي تم الرد عليها، لم يتم الإجابة على 33.5٪ من الأسئلة في المجموع. وقد نجح 188 طالبا من أصل 255 طالبا يمثلون 73.7 في المائة من الطلاب. ومن أصل 78 علامة ل سؤال متعدد الاختيارات، تم تحقيق 46.33، ومن أصل 22 علامة للمقالة 12.9 قد تحققت. وكان النجاح في الأسئلة متعدد الاختيارات، 82.9٪ في حين كان في أسئلة المقال 67.7٪ والفشل في كلا النوعين كان 12.5٪. من أصل 100 سؤال لكل من الأسئلة متعدد الاختيارات و اسئلة المقال، تم الرد على 55.07 ± 7.99 من الأسئلة متعدد الاختيارات و 51.13 ± 15.28 للمقالة. وبشكل عام بلغت نسبة الطلبة الناجحين 73.7٪، وبلغت نسبة الطلبة الفاشلين 26.3٪ الخلاصة: كان معدل النجاح لكل من الأسئلة متعدد الاختيارات وأسئلة المقال نفسه تقريبا مما أدى إلى معدل نجاح إجمالي 73.7٪ الذي يلبي نتائج الدراسات الأخرى التي أجريت مقارنة نوعي الأسئلة.